Adolescent sexting from a social learning perspective. Issue 1 (February 2017) - Van Ouytsel, Joris; Ponnet, Koen; Walrave, Michel; d'Haenens, Leen
Highlights: This study examines adolescent sexting from a social learning theory perspective. We distinguish between sexting within and outside of a romantic relationship. Attitudes and perceived peer approval are linked with engagement in sexting. Positive emotional rewards influence sexting outside of a relationship. Abstract: The purpose of this study is to analyze which components of the social learning theory are associated with adolescents' engagement in sexting among a sample of 357 respondents. Additionally, we distinguish between two types of online sexual self-disclosure: sexting within and outside of a romantic relationship. The results indicate that the extent to which adolescents hold positive attitudes towards the behavior and the extent to which they perceive that their peers approve of sexting, are associated with their engagement in sexting both within and outside of a romantic relationship, when controlling for age, gender, school track and internet use. Sexting outside of a romantic relationship was also influenced by the thrill that young people get out of engaging in this behavior. The discussion addresses the implications of these findings for prevention programs, practice and future research, such as the necessity for future studies to ask with whom participants have engaged in sexting.